Implementasi PSAK 16 Pasca Adopsi IFRS Dan Pemberian Insentif Perpajakan Pada Perusahaan BUMN Sektor Infrastruktur Di Indonesia - Lisa Angelia; Mochamad Farhan Tresna; Amrie Firmansyah (STATERA: Jurnal Akuntansi dan Keuangan, 2021)
This study explores the implementation of PSAK 16 after the IFRS adoption and the issuance of PMK No. 191/PMK.010/2015 concerning Revaluation of Fixed Assets for Taxation Purposes for Applications Filed in 2015 and 2016 as a tax incentive to encourage companies to apply revaluation method. This experimentation uses a qualitative method with a content analysis approach. The sample used is publicly traded state-owned enterprises in the infrastructure sector. Data obtained from the companies' financial statements from 2015 to 2017 were employed sourced from www.idnfinancials.com and the company's official website. Using purposive sampling, as many as 15 observations (5 companies for 3 years) were procured. As an inference, state-owned enterprises in the infrastructure sector have reported their fixed assets under PSAK 16 with complete disclosure detailing the fixed assets' measurement basis, depreciation method, estimated economic life and depreciation rate, gross carrying amount and its related accumulated depreciation at the beginning and end of the period as well as reconciliation of carrying amount. In addition, out of five companies examined, two of them applied the tax incentive in 2015 to 2016 regarding asset revaluation; they are PT Telekomunikasi Tbk. and PT Garuda Indonesia Tbk.